2010
DOI: 10.1007/s11255-010-9809-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in type III chronic prostatitis (CP) and chronic pelvic pain syndrome (CPPS) observed in Turkish patients

Abstract: Sexual function disorders, especially ejaculation disorders (EP and PEP), are frequently seen in CP/CPPS patients versus normal population. Age, symptoms period, symptom score and CP/CPPS subgroups are not risk factors for sexual function disorders. Patients with the diagnosis of CP/CPPS should be evaluated for sexual function disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…In Turkish patients with CP/CPPS types IIIa and IIIb, pain on ejaculation was detected in 37.2%, while none of the control group had pain on ejaculation [Sönmez et al 2011]. Similar results were reported in another study from USA.…”
Section: Prevalence Of Non-pe Ejd In Patients With Other Medical Condsupporting
confidence: 87%
“…In Turkish patients with CP/CPPS types IIIa and IIIb, pain on ejaculation was detected in 37.2%, while none of the control group had pain on ejaculation [Sönmez et al 2011]. Similar results were reported in another study from USA.…”
Section: Prevalence Of Non-pe Ejd In Patients With Other Medical Condsupporting
confidence: 87%
“…In comparison, ED was only associated with PE in 15.2% of these patients (123). A similar study evaluated 43 patients with type III prostatitis and found a significant difference between PE prevalence in these patients (67.44%) vs. their control group (40%) (129). An Italian study also evaluated 399 patients with symptoms that were suggestive of CP to determine prevalence of sexual dysfunction within this cohort (125).…”
Section: Urologic Risk Factorsmentioning
confidence: 92%
“…Gonen et al studied 66 patients with chronic pelvic pain syndrome in Turkey and found that the rate of PE was higher in patients in the study group than it was in subjects without PE, and this difference was statistically significant [17]. Sönmez et al reported a higher prevalence of PE in the CP/CPPS group (67.44%) than in individuals without PE (10%) [18]. In this study, we found that the prevalence of CP was 27.9% and PLS was 32.0% in patients complaining of PE, which was lower than the above-mentioned reports.…”
Section: Discussionmentioning
confidence: 97%